Remote organ injury induced by myocardial ischemia and reperfusion on reproductive organs, and protective effect of melatonin in male rats - Şahna, E; Türk, G; Ateşşahin, A; Yılmaz, S; Ölmez, E (My University, 2007)
Objective: Myocardial ischemia and reperfusion (MI-R) leads to remote organ injury associated with oxidative stress. Melatonin is a well-known antioxidant and free-radical scavenger. This study was conducted to examine whether MI-R causes damage in the testes and sperm quality, and to investigate the possible protective effect of exogenous melatonin on these parameters in an in vivo rat model. Design: Experimental study. Setting: Experimental Research Center, Fırat University Medical School, Elazıg?, Turkey. Patient(s): Eight-week-old male Wistar rats (n 18). Intervention(s): To produce MI-R, a branch of the descending left coronary artery was occluded for 30 minutes, followed by 120-minute reperfusion. Melatonin (10 mg/kg) or vehicle was given 10 minutes before ischemia via the jugular vein. Main Outcome Measure(s): Reproductive organ weights and epididymal sperm concentration, sperm motility, abnormal sperm rate, and testicular-tissue malondialdehyde (MDA) and glutathione (GSH) levels were examined after reperfusion. Result(s): MI-R significantly decreased epididymal sperm motility, and increased the testes-tissue level of MDA, compared to the control group. Administration of melatonin reversed the harmful effects of MI-R significantly. However, MI-R did not change sperm concentration, GSH levels, and reproductive organ weights. Conclusion(s): These findings indicate that MI-R leads to damage of testis tissue and sperm motility, and melatonin protects against MI-R-induced reproductive-organ injury. These results may also encourage the use of antioxidants to reduce remote organ injury in the testis after MI-R.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Melatonin myocardial ischemia and reperfusion oxidative stress sperm characteristics remote organ